Hoax Analysis on Social Media Corpus to Develop “Kapak Hoaks (Hoax Axe)” Model: A Study on Critical Discourse Analysis - Sukma Fatmawati; Rizky Salzabila; Galang Aulia Rizkitama (Universitas Dian Nuswantoro, 2020)
Abstract. In globalization era, hoax has been widely spread on social media and disturbs the well-built relationship of Indonesian people. Even it often breaks the unity of people. Lack of knowledge in how to identify hoax has let readers be hypnotized to believe that the news is real. This study is aimed to develop